Optimalisasi Fungsi Bakamla Sebagai Indonesian Coast Guard: Antara Regulasi Dan Realita - Umra, Alieffandy; Iryani, Dewi; Setiawan, Puguh Aji Hari (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
The Indonesian Maritime Security Agency (Bakamla) plays a strategic role in ensuring security, safety, and law enforcement within Indonesia’s maritime jurisdiction. Although its authority is normatively stipulated through regulations such as Law No. 32 of 2014, Presidential Regulation No. 178 of 2014, and Government Regulation No. 13 of 2022, in practice Bakamla has yet to fully function as an ideal Indonesian Coast Guard. The absence of a specific law, overlapping authorities with other agencies, and limited resources hinder its operational effectiveness. This study aims to analyse Bakamla’s legal position and authority within the national legal system, identify discrepancies between regulation and operational reality, and formulate institutional strengthening strategies. Using a normative juridical approach, this research concludes that establishing a dedicated Coast Guard Law is an urgent step to develop a unified, professional, and effective national maritime security system